2013
DOI: 10.1007/s11356-013-1747-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA damage in Brazilian workers occupationally exposed to pesticides: a study from Central Brazil

Abstract: We evaluated 41 rural workers occupationally exposed to pesticides and 32 subjects as a control group, using the micronucleus (MN) and the comet assay. For the comet assay, we evaluated the peripheral blood, and for the MN, we sampled cells from the oral epithelium. Damage to DNA was measured by tail length, % DNA in tail (% tail), olive tail moment (OTM), and tail moment (TM). The exposed group presented an 8× increase in MN frequency, when compared to the control group (p <0.05). When we contrasted the MN fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
3
17
0
1
Order By: Relevance
“…So, the occupational exposure increases cytogenetic damage induced by pesticides exposure. Researches on pesticide-exposed workers from all over the world in the last decade also demonstrated statistically signifi cant DNA damage, MN and CAs [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In a recent study, it was found an increased frequency of MN and CAs in pesticide-exposed agricultural workers from northeastern Brazil [25].…”
Section: Discussionmentioning
confidence: 99%
“…So, the occupational exposure increases cytogenetic damage induced by pesticides exposure. Researches on pesticide-exposed workers from all over the world in the last decade also demonstrated statistically signifi cant DNA damage, MN and CAs [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In a recent study, it was found an increased frequency of MN and CAs in pesticide-exposed agricultural workers from northeastern Brazil [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidance for comet assay methodology suggests that the most useful comet measurement is the percentage of DNA in the comet tail ( Anderson et al 2013 , Azqueta and Collins 2013 , Collins et al 2014 ). Only one of the six comet studies reported measurement of percentage of DNA in the comet tail ( Khayat et al 2013 ).…”
Section: General Methodologymentioning
confidence: 99%
“…However, indiscriminate use contaminates many environmental components including soil, water, air, and kills other nontargeted species. [20][21][22][23] Pesticide toxicity is of two types-acute and chronic. Among the chronic effects, severe hematotoxicity followed by BM failure and development of AA is a major health hazard in countries where a large population is economically dependent on agriculture such as India and Thailand.…”
Section: Introductionmentioning
confidence: 99%